Data quality and associated factors of routine health information system among health centers of West Gojjam Zone, northwest Ethiopia, 2021 - Chekol, Afework; Ketemaw, Asmamaw; Endale, Addisu; Aschale, Abiot; Endalew, Bekalu; Asemahagn, Mulusew Andualem (Frontiers in Health Services, 2023)
Background: Data quality is a multi-dimensional term that includes accuracy, precision, completeness, timeliness, integrity, and confidentiality. The quality of data generated by a routine health information system is still very poor in low and middle-income countries. There is a paucity of studies as to what determines data quality in health facilities in the study area. Therefore, this study was aimed to assess the magnitude of the quality of routine health information system data and its determinants among health centers. OBJECTIVE: To assess data quality and its associated factors in routine health information system among health centers of West Gojjam Zone, Northwest Ethiopia in 2021. METHOD: A facility based quantitative study design triangulated by the qualitative method was conducted. A total of 314 health professionals from 32 health centers were selected using a simple random sampling procedure. Data were gathered using a standardized checklist, interviewer administered questionnaires and key informant interviews guideline. Descriptive statistics to describe variables and binary logistic regression to identify factors associated with data quality were computed using STATA version 14. Variables with p-value of less than 0.25 in the bivariate analysis were entered to multi-variable logistic regression analysis. P-value of less than 0.05 at 95% CI was taken to declare statistically significant. Manual analysis was done for qualitative data collected from purposively selected key informants. Results: The study found that the overall data quality at health centers of West Gojjam Zone was 74% (95% CI: 68 - 78). Complexity of routine health information system format (AOR=3.8; 95%CI: 1.7-8.5), problem solving skill for RHIS tasks (AOR=2.8; 95% CI:1.2-6.4) and knowing duties, role and responsibilities were significantly associated with data quality(AOR=12; 95%CI: 5.6-25.8), and lack of human resource, poor feedback mechanisms, delay in completing data records, lack of use of data, inadequate training on health information systems were barriers affecting data quality. Conclusions: The level of data quality among public health centers in the Amhara region was less than the expected at the national level.